PENYULUHAN EDUKASI TENTANG DAGUSIBU OBAT DI GEREJA KATOLIK SANTO FRANCISCUS XAVERIUS, SEMARANG - Paulina Maya Octasari; Sisca Devi; Angela Desiani Ampur (Jurnal Pengabdian IKIFA, 2024)
Independent treatment is carried out to help improve people's health status at a more affordable cost. A good level of knowledge is required to ensure the success of self-medication therapy. A national movement regarding the drug DAGUSIBU needs to be carried out to increase public knowledge regarding good drug management to support self-medication behavior. One effort to increase knowledge is carried out through outreach activities to the community. This service activity aims to provide public knowledge about how to properly obtain, use, store and dispose of medicines. The activity stages consist of the preparation/survey, implementation, and evaluation stages. The activity will be held on Sunday, August 13, 2023 in Room A1 of St. Mary's Church Fransiscus Xaverius Kebon Dalem, Semarang and attended by 41 participants. The media used are presentation materials, pocketbooks, and drug samples. The results showed that 97,56% (40 participants) understand how to get the right medicine, but 87,80% (36 participants) are still not precise in using eye drops/ointment. There are 95,12% (39 participants) still do not know how to store and dispose of medicines properly. During the activity, participants were enthusiastic when listening to lectures and discussing. In general, educational outreach about the drug DAGUSIBU has provided additional knowledge to the public.